CORRELATION BETWEEN SADDLE ANGLE AND MINIMAL CROSS SECTION AREA OF THE UPPER AIRWAY - Khalid, Zahra; Ahmed, Usman; Anwar, Ayesha (Pakistan Journal of Physiology, 2016)
Background: The relationship between airway and facial morphology is one of the components of facial skeleton that has extensively been debated in the literature. Studying this relationship to find conclusive results has clinical importance. Hence, the current study was carried out with the objective to determine association between saddle angle and the cross-section area of upper airway as assessed on Cone beam Computed Tomography. Methods: It was a descriptive cross sectional study in which sixty patients (38 males, 22 females) who met the inclusion criteria were included through non-probability purposive sampling. Cephalometric landmarks (Nasion, Sella and Basion) were identified on the sagittal view of Cone beam Computed Tomography software to calculate the cranial base angle. The Minimal Cross-section Area of the upper airway was calculated at the level where the soft palate drops down posteriorly. Pearson correlation coefficient was applied to see the correlation between saddle angle and minimal cross section area of the upper airway, and p≤0.05 was considered significant. Results: There were 38 (63.3%) males and 22 (36.6%) females with a mean age of 30.5±14.9 years. The mean values of saddle angle and minimal cross-section area were 129.7° and 207.9 mm2 respectively. The mean value of saddle angle recorded in the females and males was 131.5°±5.9 and 128.9°±5.8 respectively and the median values were 131.6° and 129.1° respectively. There was positive and significant correlation between saddle angle and the cross-section area of upper airway (r=0.34, p=0.007). Conclusions: The cranial base angle is positively correlated with airway cross section. Saddle angle on a lateral cephalogram can give an indication of an upper airway patency problem without having need to expose the patient to an excessive radiation dosage as of a Cone Beam Computed Tomography. Pak J Physiol 2016;12(3):16–8